Comparison Between Clinical Findings and Magnetic Resonance Imaging Findings in Lumbar Prolapsed Intervertebral Disc - Banjade, Deepak; Poudel, Krishna Prasad; Adhikari, Sushan; Adhikari, Rabindra; Tamang, Ramesh Syangtan; Baral, Santosh (Nepal Orthopaedic Association Journal, 2023)
Introduction: Lumbar prolapsed intervertebral disc is commonly associated abnormality with lower backache. Disc herniation of same size can be asymptomatic in one patient and agonizing in another patient. Magnetic resonance imaging (MRI) is a gold standard diagnostic investigation for prolapsed intervertebral disc. Despite of high sensitivity sometimes MRI shows abnormal findings even in the asymptomatic individuals indicating a moderate relationship between MRI and symptoms in the patient. The study was conducted to correlate the abnormalities observed on MRI and clinical features of lumbar disc prolapse.Methodology: A descriptive cross-sectional study was conducted from 20 December 2021 to 15 September 2022. Ethical approval was obtained from the Institutional Review Committee (Reference number: 078/78-009/HG). A convenience sampling method was used. The study consisted of patients with low back pain and radiation to lower extremity or patient with MRI scan of lumbar spine. Clinical and MRI findings were correlated to know the association and significance of MR findings in producing symptoms.Results: The study included 68 patients with back pain between 18 to 55 years (mean 41± 8.79 years). Neurological symptoms were present in 26 (38.23%) patients. Disc bulge in MRI was noticed in 48 (45.28%), protrusion in 46 (43.39%) and extrusion in 10 (11.32%) levels, most seen at L5-S1 level (66.11%). The clinical level of pain distribution correlated well with the MRI level (Kappa 0.69), but not all disc bulges produced symptoms.Conclusion: Clinical features and Magnetic resonance imaging findings of disc prolapse had significant correlation similar to other studies done in a similar setting, but all imaging abnormalities may not have a clinical significance.